(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The future of enterprises depends among other things also on its rate of innovation. Particularly for the development of product ideas the innovation potential of living nature is used hardly or insufficiently during the construction process. Development teams orient themselves still too little at the evolution regularities and structure principles of biological systems. Orienting at the regularities of the evolution of biological systems as well as at the efficient principles of operation, structure and organization of living nature could supply various suggestions for new product ideas. For this reason the author of this contribution conceived a construction bionics, which helps the development engineer to use living nature systematically and purposefully as source of inspiration.